Partisipasi Ibu Rumah Tangga Dalam Meningkatkan Ekonomi Keluarga Melalui Pekerjaan Pengupas Bawang - Khansa Humaira Nazwa Lubis (KESKAP: Jurnal Kesejahteraan Sosial, Komunikasi dan Administrasi Publik, 2026)
This study aims to examine the participation of housewives in improving family economy through onion peeling work on Jalan Selamat Ketaren MMTC. The research used a descriptive qualitative method involving three housewives as informants. Data were collected through interviews, observation, and documentation. The findings show that onion peeling is a flexible economic activity because it can be carried out while maintaining domestic responsibilities. Although the income earned is relatively small and unstable, it still contributes to daily household needs, children’s education expenses, and helps reduce the husband’s economic burden. This participation also strengthens the economic resilience of the family.